Importance of Gymnasium Students’ Anxiety, Identity Style and Stress Coping Strategies for Examination Stress Assessment - Mazilauskaite, Ruta (Jaunųjų mokslininkų darbai, 2021)
Examinations and their results often become perhaps the biggest challenge in young person’s life, which is associated with the course of later life. For this reason, a high level of stress is observed, which is maintained by both personal and situational factors. In this context, the objective of this study is to identify the links between the experienced anxiety, identity style, examinations stress and its coping strategies of the gymnasium students. The study involved 175 gymnasium students in grades 10 to 12. Of these, 109 were girls (62.3%) and 66 were boys (37.7%), aged 16 to 19 years of age (M = 17.27, SD = 0.92). Gymnasium students were given a questionnaire based on the State-Trait Anxiety Inventory (Spielberger, Gorsuch, Lushene, 1970), Identity Style Inventory Version 5 (ISI-5) (Berzonsky, Soenens, Luyckx, Smits, Papini, Goossens, 2013), the Stress Coping Questionnaire (Grakauskas, Valickas, 2006), and the Examination Stress Scale for Adolescent Students (Sung, Chao, 2014). It was found that the more frequent experience of stress in gymnasium students examinations was predicted by stronger trait and state anxiety, more frequent choice of informational, normative identity processing style and more frequent use of avoidance strategy in experiencing stress.